2017
DOI: 10.3389/fpls.2017.00994
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Aeluropus littoralis AlSAP Gene Enhances Rice Yield under Field Drought at the Reproductive Stage

Abstract: We evaluated the yields of Oryza sativa L. ‘Nipponbare’ rice lines expressing a gene encoding an A20/AN1 domain stress-associated protein, AlSAP, from the halophyte grass Aeluropus littoralis under the control of different promoters. Three independent field trials were conducted, with drought imposed at the reproductive stage. In all trials, the two transgenic lines, RN5 and RN6, consistently out-performed non-transgenic (NT) and wild-type (WT) controls, providing 50–90% increases in grain yield (GY). Enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Similar findings were reported in Arabidopsis, where OsSAP1 from rice protected yields during water stress (Giri et al 2011). Upregulation of the A. littoralis, AlSAP gene in rice, also enhanced grain yield by 50-90% under drought stress in the field (Ghneim-Herrera et al 2017). The expression of Prunus persica, PpSAP1, was induced by heat and water stress and increased water retention ability in transgenic plums (Lloret et al 2017).…”
Section: Stress-associated Proteins (Saps)supporting
confidence: 72%
See 1 more Smart Citation
“…Similar findings were reported in Arabidopsis, where OsSAP1 from rice protected yields during water stress (Giri et al 2011). Upregulation of the A. littoralis, AlSAP gene in rice, also enhanced grain yield by 50-90% under drought stress in the field (Ghneim-Herrera et al 2017). The expression of Prunus persica, PpSAP1, was induced by heat and water stress and increased water retention ability in transgenic plums (Lloret et al 2017).…”
Section: Stress-associated Proteins (Saps)supporting
confidence: 72%
“…SAP gene products may be involved in stress signaling through stable protein-protein interactions with zinc finger motifs (Kothari et al 2016). SAPs may emerge as novel targets for improving stress tolerance, specifically with stress-responsive promoters (Ghneim-Herrera et al 2017). Functional analysis of the ShSAP1 gene from sugarcane indicated that ShSAP1 might confer drought and osmotic stress tolerance in transformed tobacco (Li et al 2014b).…”
Section: Stress-associated Proteins (Saps)mentioning
confidence: 99%
“…Overexpression of AtSAP5 in cotton also improved the tolerance to water deficit and heat stress (Hozain et al, ). Further, recently it has been shown that overexpression of A. littoralis AlSA P gene also increased 50–90% rice grain yield under field drought conditions (Ghneim‐Herrera et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Mitotic chromosomes were prepared from root tips which pretreated in ice water for 24 The Arabidopsis-type telomere probe was labelled with uorophore ATTO488 using nick translation labelling kit (Jena Bioscience). Fluorescence in situ hybridization was performed as described in [38] with pretreatment for 10 min in 45% acetic acid at room temperature, followed by 0.1% pepsine in 0.01N HCl at 37°C.…”
Section: Chromosome Preparation and Uorescence In Situ Hybridizationmentioning
confidence: 99%
“…These knowledge can potentially be used for improving tolerance to abiotic stresses in economically important crops [21]. Several morphological, anatomical, ecological, and physiological traits of A. littoralis have been investigated so far [16,22,23] and also the transfer of stress related genes to other species resulted in enhanced stress resistance [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%